2010
DOI: 10.1111/j.1469-0691.2009.02813.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus lugdunensis in several niches of the normal skin flora

Abstract: Staphylococcus lugdunensis is a coagulase-negative staphylococcus (CNS). Its pathogenicity and virulence are more similar to Staphylococcus aureus than to a CNS. It causes severe infections with high mortality, such as endocarditis, but more often painful and prolonged skin- and soft-tissue infections. Little is known of its normal habitat. Whether it is an integral part of the normal skin flora like many other CNS has been questioned, since it is rarely seen in blood cultures. This study was designed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 16 publications
2
70
0
1
Order By: Relevance
“…S. lugdunensis has also been reported as a cause of skin and soft tissue infections, particularly involving the breast, abdomen, and lower limbs (1,2,4), and has been identified as an agent of prosthetic joint infection (10). In keeping with these reports, studies that have screened healthy persons for carriage have confirmed identification from skin of the abdomen, groin, and lower extremities (3,12).…”
Section: S Lugdunensis Is a Coagulase-negativesupporting
confidence: 53%
“…S. lugdunensis has also been reported as a cause of skin and soft tissue infections, particularly involving the breast, abdomen, and lower limbs (1,2,4), and has been identified as an agent of prosthetic joint infection (10). In keeping with these reports, studies that have screened healthy persons for carriage have confirmed identification from skin of the abdomen, groin, and lower extremities (3,12).…”
Section: S Lugdunensis Is a Coagulase-negativesupporting
confidence: 53%
“…This study demonstrates that, although they are both integral skin flora, S. lugdunensis and S. aureus differ in their site and frequency of colonisation. 12 The clinical relevance of S. lugdunensis was first described when it was implicated as a causative organism in endocarditis. 13 Since this time more than 80 further case reports of S. lugdunensis endocarditis have been reported, primarily involving native left-sided valves.…”
Section: Discussionmentioning
confidence: 99%
“…S. lugdunensis is recovered from the normal skin flora (1), and numerous infections have been related to inguinal-area carriage (37). Cutaneous infections account for more than 50% of S. lugdunensis infections (38), but tissue infections with various abscess localizations are reported, with tissue damage or poor clinical outcome (13).…”
Section: S Ince Its First Description In 1988 Staphylococcus Lugdunementioning
confidence: 99%